Body shape and performance on the US Army Combat Fitness Test: Insights from a 3D body image scanner. - Maria Smith; Dusty Turner; Charlotte Spencer; Nicholas Gist; Sarah Ferreira; Kevin Quigley; Tyson Walsh; Nicholas Clark; William Boldt; Justin Espe; Diana M Thomas (PLoS ONE, 2023)
Objective To identify relationships between body shape, body composition, sex and performance on the new US Army Combat Fitness Test (ACFT). Methods Two hundred and thirty-nine United States Military Academy cadets took the ACFT between February and April of 2021. The cadets were imaged with a Styku 3D scanner that measured circumferences at 20 locations on the body. A correlation analysis was conducted between body site measurements and ACFT event performance and evaluated using Pearson correlation coefficients and p-values. A k-means cluster analysis was performed over the circumference data and ACFT performance were evaluated between clusters using t-tests with a Holm-Bonferroni correction. Results The cluster analysis resulted in 5 groups: 1. "V" shaped males, 2. larger males, 3. inverted "V" shaped males and females, 4. "V" shaped smaller males and females, and 5. smallest males and females. ACFT performance was the highest in Clusters 1 and 2 on all events except the 2-mile run. Clusters 3 and 4 had no statistically significant differences in performance but both clusters performed better than Cluster 5. Conclusions The association between ACFT performance and body shape is more detailed and informative than considering performance solely by sex (males and females). These associations may provide novel ways to design training programs from baseline shape measurements.